If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(y+4)=y-7+4(3y+1)
We move all terms to the left:
-2(y+4)-(y-7+4(3y+1))=0
We multiply parentheses
-2y-(y-7+4(3y+1))-8=0
We calculate terms in parentheses: -(y-7+4(3y+1)), so:We get rid of parentheses
y-7+4(3y+1)
determiningTheFunctionDomain y+4(3y+1)-7
We multiply parentheses
y+12y+4-7
We add all the numbers together, and all the variables
13y-3
Back to the equation:
-(13y-3)
-2y-13y+3-8=0
We add all the numbers together, and all the variables
-15y-5=0
We move all terms containing y to the left, all other terms to the right
-15y=5
y=5/-15
y=-1/3
| 3(2x-4)=-3x+9 | | 4(2x-1)+6=10 | | -8+7u=-8-10 | | -3x-30+10x=5 | | -1=-6(k-7)+6(k-8) | | 6y+18=4(y-2 | | -5(4x-8)+6x=4(x+8) | | -5(-3w+1)-3w=2(w-9)-3 | | 2x)+(5x-23)+(5x+5)=180 | | n+16=–3n | | d/12+9=15 | | 60=3(-8a+4) | | -5(-3w+1)-3w=2+(w-9)-3 | | 5a-(3a+6)=2a+6. | | (3/4)x=2 | | 5(8x+4)+7=267 | | (3m-4)+(4m+4)= | | 7+7n=-8+4n | | n/282.4=713.4 | | x/5−9=−4 | | -4(8+6x)+24x=154 | | 14=Y/x | | -9-9r=-1-8r | | 3(4n–3)=15 | | 15=7x-4+x-3 | | 6x+3=4x−1 | | 0.20x+1.80=0.15x+2.10 | | 16=x+10+5x | | –3d=21 | | 9x-36=7(x+2) | | x*12-43-85=246 | | -7u+9-10u=-18 |